INSTRUCT A CULTURE OF LITERACY FROM AN EARLY AGE BY STORIYTELLING - Nurul Fikriati Ayu Hapsari; Baiq Arwindy Prayona; Alpina Damayanti (JOURNAL OF PROGRESSIVE INNOVATION LIBRARY SERVICE, 2025)
The low literacy rate of children in Indonesia demonstrates the need for strategic efforts to foster reading interest from an early age. Storytelling is an effective method for stimulating children's literacy skills, as it develops language, imagination, and moral values through a fun and communicative medium. This community service activity aims to foster a culture of literacy through mentoring storytelling activities for teachers and parents at the Al-Amin PAUD in Jurit Baru Village, Pringgasela District, East Lombok, as the implementation partner. The methods used include interactive lectures, discussions, storytelling practice, as well as mentoring and evaluation. The program was implemented in stages, starting from socializing the importance of literacy, training in storytelling techniques, providing age-appropriate reading books, and mentoring implementation in the classroom. The results of the activity showed an increase in the knowledge and skills of teachers and parents in using storytelling as a literacy medium. Children became more enthusiastic about reading, dared to tell stories, and were able to understand the content of the stories better. This activity also strengthened the relationship between teachers, parents, and children in building a culture of literacy in the school and home environment. The results of this community service confirm that storytelling is not merely entertainment, but an effective educational tool for instilling a love of literacy and character-building in children from an early age. Therefore, storytelling mentoring needs to be developed sustainably in other early childhood education institutions to create a literate generation with intelligence and character.